IMPACT OF DIVIDEND POLICY ON FIRM PERFORMANCE: MODERATING ROLE OF CREDIT RISK - I Kadek Bagiana; RR. Maria Yulia Dwi Rengganis; Luh Putri Mas Mirayani; Luh Pande Eka Setiawati (Jurnal Akuntansi dan Bisnis, 2025)
This study examines the impact of Dividend Payout Ratio (DPR) on firm performance, measured by Return on Assets (ROA), in Indonesian banking companies, with Non-Performing Loans (NPL) as a moderating variable. Using secondary data from the financial statements of 11 banks listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023, this research employs Moderating Regression Analysis (MRA) to test three hypotheses. The results indicate that DPR has a significant positive effect on ROA, supporting the hypothesis that higher dividend payouts enhance firm performance by attracting and retaining investors and signaling financial health. Conversely, NPL does not have a statistically significant direct effect on ROA, nor does it moderate the relationship between DPR and ROA. This suggests that while DPR is crucial for improving firm performance, the role of credit risk, as measured by NPL, does not significantly alter this relationship in the context of the studied banking companies. The R-squared value of the regression model is approximately 0.53, indicating that DPR and NPL explain 53% of the variability in ROA. These findings imply that dividend policies can be pursued independently of the current levels of non-performing loans, simplifying decision-making processes regarding dividend strategies. However, banks must continue to manage NPLs effectively for overall financial health. The study's limitations include a limited sample size and the exclusion of other potential moderating variables, suggesting areas for future research to provide a more comprehensive understanding of the factors influencing firm performance in the banking sector.